2002
DOI: 10.1103/physrevb.65.245205
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic description of shallow levels in semiconductors

Abstract: The wave function and binding energy for shallow donors in GaAs are calculated within the tight binding ͑TB͒ approach, for supercells containing up to two million atoms. The resulting solutions, coupled with a scaling law, allow extrapolation to the bulk limit. A sharp shallow-deep transition is obtained as the impurity perturbation increases. The model allows investigating the quantitative consistency between the effective mass theory and the TB formalism. Although the calculated binding energies are in excel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…We learned that similar results have been obtained independently with different methods by A.S. Martins et al 19 and L.M. Kettle et al 20 …”
supporting
confidence: 73%
“…We learned that similar results have been obtained independently with different methods by A.S. Martins et al 19 and L.M. Kettle et al 20 …”
supporting
confidence: 73%
“…Recently, calculations of a silicon donor in an electric field in the tight binding approach have been presented 28 . This approach seems to be a useful alternative to calculations based on effective mass theory.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the tight-binding (TB) approach, traditionally adopted for deep levels, 5 provides a valid description for intermediate 6,7 and shallow levels 8 in semiconductors. Impurity states are calculated from a sequence of supercell sizes and a finite-size analysis which provides extrapolation to the bulk limit.…”
Section: Introductionmentioning
confidence: 99%